Editorial (2005)
Our readers might have seen several changes in the layout and organization of our journal in the last three years. This has been done not only to fulfil the requirements of international scientific journals, but to respond to the increasing interest of pre and in-service teachers from Colombia as well as from other countries, and those who want to learn about the teaching and learning experiences reported in our publication. This has shown, as Ann Burns states, our teacher community acknowledges our work and, in turn, has been encouraged to publicize projects carried out in our field.